Knowledge, perceptions and behaviours about skin cancer and sun protection among secondary school students from Central Italy. (20th February 2012) - Suppa, M.; Cazzaniga, S.; Fargnoli, M.C.; Naldi, L.; Peris, K.
Abstract Background Although sun exposure is a strong risk factor for skin cancer, tanning is very popular among adolescents. Awareness of skin cancer and sun exposure might influence sun protective behaviours in this population. Objectives To investigate the awareness of skin cancer and sun‐safe practices among Italian adolescents. Methods A questionnaire about knowledge of skin cancer, perceived severity of sun rays/skin cancer and behaviour toward sun protection was administered to 1204 secondary school students. Predictors of these three components were assessed by case‐control analyses considering different combinations of answers. Multiple logistic regression models were used to this scope. Results The majority of participants had heard of skin cancer in the past (97.0%), correctly identified possible causes (58.6%) and names (64.2%) of skin cancers and judged appropriately the perceived danger of sunrays (70.2%) and skin cancer (80.6%). Nonetheless, students' behaviour was poor: only 13.5% stated to always use sun‐safe practices and 39.1% never used any. Independent predictors of proper knowledge were: Lyceum school, and family or TV/media as information source; of appropriate perceived severity: Lyceum school, a darker skin type, and dermatologists as information source; of acceptable behaviour: female sex, a darker skin type, and dermatologists or general practitioners (GPs) as information source. Conclusions Despite a fairly good knowledge about skin cancer and sun exposure, students' behaviour was unsatisfactory. Knowledge is not sufficient to produce a positive behaviour, as determinants of these two aspects are different. Dermatologists and GPs should be considered as key‐figures for future multicomponent intervention strategies in this field.